Men's health: non-communicable chronic diseases and social vulnerability - Pacharone Bertolini Bidinotto, Daniele Natalia; Simonetti, Janete Pessuto [UNESP]; Mangini Bocchi, Silvia Cristina [UNESP] (Univ Sao Paulo, Escola De Enfermagem De Ribeirao Preto, 2016)
Objectives: to evaluate the relationship between absences in scheduled appointments and the number of non-communicable chronic diseases and to investigate the relationship between spatial distribution of these diseases and social vulnerability, using geoprocessing. Method: a quantitative study of sequential mixed approach by analyzing 158 medical records of male users to relate the absences and 1250 medical records for geoprocessing Results: the higher the number of absences in the scheduled medical appointments, the less were the number of non-communicable chronic diseases and the ones listed in the International Classification of Diseases in single men. There were 21 significant geostatistically cases of glucose intolerance in the urban area. Of these, 62% lived in a region with a social vulnerability rating of Very Low, Medium 19%, 14% Low and 5% High. Conclusion: it was observed that the older the men, the greater is the number of chronic diseases and the less they miss scheduled appointments. Regarding the use of geoprocessing, we obtained a significant number of cases of glucose intolerance in urban areas, the majority classified as Very Low social vulnerability. It was possible to relate the spatial distribution of these diseases with the social vulnerability classification; however, it was not possible to perceive a relationship of them with the higher rates of social vulnerability.
Keywords: Men's Health; Primary Health Care; Geographic Mapping